1999
DOI: 10.1001/archpsyc.56.6.537
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Abnormalities in Schizophrenia Identified by Structural Magnetic Resonance Imaging

Abstract: Findings using our methods have implications for understanding brain abnormalities in schizophrenia and suggest the importance of the paralimbic areas and their connections with prefrontal brain regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
191
1
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(218 citation statements)
references
References 73 publications
18
191
1
8
Order By: Relevance
“…Volumetric measures were then extracted by the application of the probabilistic HO Cortical Structural Atlas that defines 48 cortical regions on a normalized brain (as distributed with the FSL software package http://www.cma.mgh.harvard.edu/fsl_ atlas.html). The cortical parcellations for this atlas were originally described in (Goldstein, Goodman, et al, 1999, Goldstein, Seidman, et al, 2007. We split each of the 48 regions of the HO atlas at the centre of the left-right axis, to produce 48 regions for each cerebral hemisphere.…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Volumetric measures were then extracted by the application of the probabilistic HO Cortical Structural Atlas that defines 48 cortical regions on a normalized brain (as distributed with the FSL software package http://www.cma.mgh.harvard.edu/fsl_ atlas.html). The cortical parcellations for this atlas were originally described in (Goldstein, Goodman, et al, 1999, Goldstein, Seidman, et al, 2007. We split each of the 48 regions of the HO atlas at the centre of the left-right axis, to produce 48 regions for each cerebral hemisphere.…”
Section: Image Processingmentioning
confidence: 99%
“…Column (a) depicts the results from males only, column (b) from females and column (c) the results from males and females meta-analysed. Goodman, et al, 1999;Goldstein, Seidman, et al, 2007). It therefore contained asymmetrical definitions for structures that showed different sizes or locations between the left and right hemispheres in the reference dataset (including the PT; Fig.…”
Section: 2mentioning
confidence: 99%
“…MRI findings of frontal lobe volume deficits in schizophrenia have been relatively inconsistent, with several studies reporting reduced volume in schizophrenia and others reporting no significant differences (Goldstein et al, 1999;McCarley et al, 1999;Shenton et al, 2001). Although a few studies have evaluated subregions within the frontal lobe, Buchanan et al (1998) reported volume reductions in prefrontal WM as well as right and left inferior gyri volume reduction in schizophrenia.…”
Section: Cortical Thickness Abnormalities In Schizophreniamentioning
confidence: 99%
“…1 Support for dysfunction in this brain region at the imaging, cellular and molecular level in schizophrenia [2][3][4][5] and bipolar disorder [6][7][8] is very strong.…”
Section: Introductionmentioning
confidence: 99%